Metasurface-assisted multimodal quantum imaging - Yifan Zhou; Xiaoshu Zhu; Tianyue Li; Zhou Zhou; Qianhui Bi; Jun Liu; Jian Chen; Boyan Fu; Juanzi He; Xiaojing Feng; Xinyang Feng; Xingyu Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Traditional quantum imaging is featured by remarkable sensitivity and signal-to-noise ratio, but limited by bulkiness and static function (either phase contrast imaging or edge detection). Our report synergizes a polarization-entangled source with a metasurface consisting of various sophisticatedly engineered spatial frequency segments. By tuning polarization, we demonstrate multiple “on”-state quantum imaging modes, enabling flexible switching between phase contrast, edge, and arbitrary superimposed imaging mode. Furthermore, the “off”-state, which characterizes the background noise, enables self-calibration of the system by subtracting this noise in “on”-state modes, resulting in self-enhanced edge detection. Our approach performs phase contrast imaging with a phase difference of π/4 present in the target object, and edge imaging capable of detecting tiny (radius about 2 μm) defects, maintaining high image contrast (phase contrast of 0.726, and enhanced edge contrast of 0.902). Our results provide insights into constructive duet between quantum imaging and metaoptics.